Pemilihan Acacia mangium untuk Sumber Benih dengan Teknik Analisis Bip dan Korespondensi di Parungpanjang, Bogor, Jawa Barat Selection of Acacia mangium Willd. Provenances for Seed Source by Technique of Bi-plot and Correspondence Analysis at Parungpanjang, Bogor, West Java - Nurhasybi Nurhasybi; Dede J Sudrajat; Komar Diatna (Jurnal Manajemen Hutan Tropika, 2008)
Provenance trials is one of planting test activities aimed at finding the best provenance in a certain area of forest plantations. The best provenances can be used for establishing the seed sources in the location. The objective of this research was to identify the character or trait performed in every provenance of A. mangium to the observed variable and to see the relation between variables in order to find the potential provenances that can be developed as seed sources. Provenance trials stand as an object for this research was planted in 1995 in Parung Panjang Forest Research Area with Completely Random Block Design. The spacing in planting between trees was 3 metres located at 3 blocks. Number of provenances to be observed were 15 provenance. In every provenance was taken 5 trees sample randomly that equal to 75 trees in each block as representave of every provenance. Totally the sample trees was 225 trees from the 3 blocks. The variables to be observed in this research were tree height (X1), clear bole (X2), tree diameter (X3), tree volume (X4), stem form (X5), branching system (X6), dan bentuk tajuk (X7). Analisis yang digunakan dalam penelitian ini adalah analisis biplot dan korespondensi.